Descriptions of five new species of Helina Robineau-Desvoidy (Diptera: Muscidae) from China - Xue, Wan-qi; Du, Jing; Zhang, Lu (Entomologica Fennica, 2008)
In this paper, five new species belonging to the genus Helina Robineau-Desvoidy are described and illustrated, viz H. combinisetata sp. n., H. discombinisetata sp. n., H. flavipulchella sp. n., H. subsetiventris sp. n., H. xingkaiensis sp. n. Revised couplets for the key to known Chinese species are given.